60th anniversary of the Faculty of Dentistry of Pavlov University - I. N. Antonova; S. V. Vasil’ev; I. A. Gorbacheva; L. Yu. Orekhova; T. B. Tkachenko; V. N. Trezubov; S. B. Ulitovskiy; A I. Yaremenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
60th anniversary of the Faculty of Dentistry of Pavlov University.